ISOLATION AND IDENTIFICATION OF ANTIOXIDANT COMPOUNDS FROM METHANOL EXTRACT OF SAPPAN WOOD (Caesalpinia sappan) - Agung Wibawa Mahatva Yodha; Muamar Abdillah; Astrid Indalifiany; Elfahmi Elfahmi; Sahidin Sahidin (Jurnal Farmasi Sains dan Praktis, 2021)
Sappan wood extract (Caesalpinia sappan) provides better antioxidant properties than ascorbic acid. Empirically, Sappan wood is often used as traditional medicine. To support the utilization of Sappan wood, the isolation and identification of active antioxidant compounds from the methanol extract of Sappan wood had been conducted from this study. Extraction was performed with maceration and evaporation methods. The spots of active antioxidant compounds in TLC-DPPH observations were isolated using liquid vacuum chromatography to obtain two pure compounds. The results of the LC-MS/MS identification of the two compounds, respectively, exhibited peak fragmentation of molecular ions at m/z 271.09, 257.15, 167.03, 151.06, 123.12, and 104.06 at the retention time of 6.35 minutes which were translated as Alpinetine and peak fragmentation of molecular ion at m/z 287.09, 177.06, 164.05, 123.04 and 110.04 at a retention time of 5.75. minutes which were translated as 3-Deoxysappanone B. The antioxidant activity quantitatively showed that Alpinetine and 3-Deoxysappanone B were capable of scavenging DPPH radicals with IC50 values ​​of 20.11 M and 15.28 M, respectively.